Safe implementation of minimally invasive pancreas resection: a systematic review. Issue 5 (May 2020) - Moekotte, Alma L.; Rawashdeh, Arab; Asbun, Horacio J.; Coimbra, Felipe J.; Edil, Barish H.; Jarufe, Nicolás; Jeyarajah, D. Rohan; Kendrick, Michael L.; Pessaux, Patrick; Zeh, Herbert J.; Besselink, Marc G.; Abu Hilal, Mohammed; et al.
Abstract: Background: Minimally invasive pancreas resection (MIPR) has been expanding in the past decade. Excellent outcomes have been reported, however, safety concerns exist. The aim of this study was to define prerequisites for performing MIPR with the objective to guide safe implementation of MIPR into clinical practice. Methods: This systematic review was conducted as part of the 2019 Miami International Evidence-Based Guidelines on Minimally Invasive Pancreas Resection (IG-MIPR). PubMed, Embase and Cochrane databases were searched for literature concerning the implementation of MIPR between 1946 and November 2018. Quality assessment was according to The Scottish Intercollegiate Guidelines Network (SIGN). Results: Overall, 1150 studies were screened, of which 32 studies with 8519 patients were included in this systematic review. Training programs for minimally invasive distal pancreatectomy, laparoscopic pancreatoduodenectomy and robotic pancreatoduodenectomy have been described with acceptable outcomes during the learning curve and improved outcomes after training. Learning curve studies have revealed an association between growing experience and improving perioperative outcomes. In addition, the association between higher center volume and lower mortality and morbidity has been reported by several studies. Conclusion: When embarking on MIPR, it is recommended to participate in a dedicated training program, to assure a sufficient volume, especially when implementing minimally invasive pancreatoduodenectomy, (20 procedures recommended annually), and prospectively collect and closely monitor outcomes for continuous quality assessment, this can be achieved through institutional databases and participation in national or international registries.